2011
DOI: 10.3109/10428194.2011.603444
|View full text |Cite
|
Sign up to set email alerts
|

Role of [18F]-fluoro-2-deoxy-d-glucose positron emission tomography in early and late therapy assessment of patients with advanced Hodgkin lymphoma treated with bleomycin, etoposide, adriamycin, cyclophosphamide, vincristine, procarbazine and prednisone

Abstract: The prognostic value of positron emission tomography (PET) in early therapy response assessment, after completion of chemotherapy and 3 months after the end of treatment in advanced Hodgkin lymphoma (HL) remains to be defined. We report the results of 69 patients with first presentation of advanced HL. [18F]-fluoro-2-deoxy-d-glucose (FDG)-PET scan was performed after four cycles (PET-4), on completion of chemotherapy after 6/8 cycles (PET-6/8) and 3 months after the completion of chemotherapy (PET 3-months). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 24 publications
1
25
0
6
Order By: Relevance
“…Considering the common finding of persistent masses on CT scan, the assessment of response and, consequently, the disease status, often represent a problem among patients diagnosed with HL due to the difficulties in distinguishing fibrotic tissue from active disease (31). In addition to PET scan, which is a technique based on tumor metabolic rate to distinguish fibrotic tissue from residual masses (32,33), gallium scan has been successfully used for several years for this purpose in patients with HL following standard chemotherapy and prior to autologous hematopoietic transplantation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the common finding of persistent masses on CT scan, the assessment of response and, consequently, the disease status, often represent a problem among patients diagnosed with HL due to the difficulties in distinguishing fibrotic tissue from active disease (31). In addition to PET scan, which is a technique based on tumor metabolic rate to distinguish fibrotic tissue from residual masses (32,33), gallium scan has been successfully used for several years for this purpose in patients with HL following standard chemotherapy and prior to autologous hematopoietic transplantation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies performed PET scans after 2 cycles of chemotherapy (PET-2) and at the completion of therapy and follow-up. The value of interim imaging at other points during treatment has been compared with that of PET-2; PET-1 has been shown to be prognostically inferior (12), whereas PET-4 has been comparable (13,14). PET-2 has therefore come to be the most common and well-validated interim response measurement in HL.…”
Section: Interim Response Assessment In Hlmentioning
confidence: 99%
“…The efficacy of BEACOPP regimen intensification in PET-2-positive patients with advancedstage HL during ABVD therapy is currently being tested in several multicenter clinical trials whose results are pending (Table 2). Four studies have reported the results of a PET-adapted strategy in this population (33,(47)(48)(49).…”
Section: Advanced-stage Hlmentioning
confidence: 99%
“…In the HD15 trial from the GHSG, a subset of 69 patients who had newly diagnosed clinical stage III, IV, or IIB HL with a large mediastinal mass or extranodal disease were treated with either 8 (n 5 35) or 6 (n 5 24) cycles of escalated BEACOPP or with 8 cycles of BEACOPP14 (n 5 10), and interim PET after 4 cycles proved to have quite a high NPV for PFS (47). Similar to the IHP criteria, 18 F-FDG uptake above the level of the mediastinal blood pool was considered PET-positive.…”
Section: Advanced-stage Hlmentioning
confidence: 99%